The Escalating Magnitude of COVID-19 Infections among the Northeastern Ethiopia Region: A Community-Based Cross-Sectional Study - Zeleke Geto; Saba Gebremichael; Melaku Ashagrie Belete; Alemu Gedefie; Genet Molla; Melkam Tesfaye; Wondmagegn Demsiss; Daniel Gebretsadik (International Journal of Microbiology)
Background. The novel coronavirus disease (COVID-19) is lethal and extremely contagious, with a rapidly rising global prevalence. The World Health Organization has declared the outbreak a global pandemic; it is reported to have spread to nearly every country in the world. However, the prevalence varies across developed and developing countries, as well as within different regions of the same country. It is not hidden that estimating the magnitude of COVID-19 infection from the community surveys is critical for public health policymakers to make decisions to deal with the outbreak, optimize measures, and design mitigation plans. Methods. A community-based cross-sectional study was conducted from 01 July to 31 August 2020 in the northeastern Ethiopia region. A simple random sampling technique was used to select study participants from the community survey, contact traces from confirmed cases, and infection suspects. After extraction of viral nucleic acid from oropharyngeal specimen, the real-time fluorescent polymerase chain reaction (RT-PCR) kit was used for detecting novel coronavirus. Results. A total of 8752 study participants were included in this study. About 63.6% were males and 36.4% were females. Out of the total 8752 study participants, 291 (3.3%) were found to be infected with the virus. The first laboratory-confirmed cases of COVID-19 were detected in the fourth week of the study period, that is, from July 24 to July 31, 2020, and the peak prevalence was observed in the last two weeks. The COVID-19 infection was more prevalent among males and in the age group of 36–52 years. Participants tested via contact trace had 1.65 times (AOR = 1.65, 95% CI = 1.09–2.51, P=0.018) the likelihood of COVID-19 infection in comparison to the other forms of community surveys. Conclusion. The trend in the prevalence of COVID-19 infection in the northeastern region has shown increment, and increasing testing capacity has a greater benefit in identifying early infection for the prevention, treatment, and control of the international pandemic.